Human papillomavirus genotype contribution to cervical cancer and precancer: Implications for screening and vaccination in Japan. Issue 7 (21st May 2020) - Onuki, Mamiko; Matsumoto, Koji; Iwata, Takashi; Yamamoto, Kasumi; Aoki, Yoichi; Maenohara, Shoji; Tsuda, Naotake; Kamiura, Shoji; Takehara, Kazuhiro; Horie, Koji; Tasaka, Nobutaka; Yahata, Hideaki; et al.
Abstract: To obtain baseline data for cervical cancer prevention in Japan, we analyzed human papillomavirus (HPV) data from 5045 Japanese women aged less than 40 years and diagnosed with cervical abnormalities at 21 hospitals during 2012‐2017. These included cervical intraepithelial neoplasia grade 1 (CIN1, n = 573), CIN2‐3 (n = 3219), adenocarcinoma in situ (AIS, n = 123), and invasive cervical cancer (ICC, n = 1130). The Roche Linear Array was used for HPV genotyping. The HPV type‐specific relative contributions (RCs) were estimated by adding multiple infections to single types in accordance with proportional weighting attributions. Based on the comparison of type‐specific RCs between CIN1 and CIN2‐3/AIS/ICC (CIN2+), RC ratios were calculated to estimate type‐specific risks for progression to CIN2+. Human papillomavirus DNA was detected in 85.5% of CIN1, 95.7% of CIN2‐3/AIS, and 91.2% of ICC. Multiple infections decreased with disease severity: 42.9% in CIN1, 40.4% in CIN2‐3/AIS, and 23.7% in ICC ( P  < .0001). The relative risk for progression to CIN2+ was highest for HPV16 (RC ratio 3.78, 95% confidence interval [CI] 3.01‐4.98), followed by HPV31 (2.51, 1.54‐5.24), HPV18 (2.43, 1.59‐4.32), HPV35 (1.56, 0.43‐8.36), HPV33 (1.01, 0.49‐3.31), HPV52 (0.99, 0.76‐1.33), and HPV58 (0.97, 0.75‐1.32). The relative risk of disease progression was 1.87 (95% CI, 1.71‐2.05) for HPV16/18/31/33/35/45/52/58, but only 0.17 (95% CI, 0.14‐0.22) for HPV39/51/56/59/66/68. Human papillomavirus 16/18/31/33/45/52/58/6/11 included in a 9‐valent vaccine contributed to 89.7% (95% CI, 88.7‐90.7) of CIN2‐3/AIS and 93.8% (95% CI, 92.4‐95.3) of ICC. In conclusion, our data support the Japanese guidelines that recommend discriminating HPV16/18/31/33/35/45/52/58 genotypes for CIN management. The 9‐valent vaccine is estimated to provide over 90% protection against ICC in young Japanese women. Abstract : We updated HPV type‐specific risks of and contributions to cervical cancer and precancer in Japan, using a large dataset from young Japanese women with cervical abnormalities. The relative risk for progression to cervical cancer and precancer was the highest for HPV16, followed by HPV31, HPV18, HPV35, HPV33, HPV52 and HPV58. The new 9‐valent vaccine is estimated to provide over 90% protection against invasive cervical cancer among Japanese women up to an age of 40 years.